Estrategias de afrontamiento y niveles de estrés asistencial en el personal de salud del Hospital La Misericordia de Calarcá (2021)
The objective of the research carried out was to establish the coping strategies and the levels of care stress presented by the health personnel of the Hospital La Misericord de Calarcá Quindío, with an analytical empirical approach, quantitative and descriptive methodology; The sample consisted of 30 health professionals and technicians; The instruments used were the modified Coping strategy scale (EEC-M) and the stress evaluation questionnaire of the Battery of Psychosocial Risks, of the Ministry of Social Protection and the Universidad Pontificia Javeriana of the city of Bogotá (2010) .